1997
DOI: 10.1007/s11738-997-0012-y
|View full text |Cite
|
Sign up to set email alerts
|

Differences in drought tolerance between cultivars of field bean and field pea. A comparison of drought-resistant and drought-sensitive cultivars

Abstract: Relatively little research has been conducted to determine different responses to drought among cultivars of the legume species. The objective of this study was to identify differences in seedlings growth, water relations and leaf conductances resulting from drought imposed on two field bean and two field pea cultivars that had been observed to differ in their drought tolerances, and special emphasis was placed on the root system development.Distinct differences between resistant and sensitive cultivars of fie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 20 publications
0
18
0
1
Order By: Relevance
“…These cultivars, all semi-dwarf, were selected on the basis of previous studies according to their possible tolerance or susceptibility to water stress in controlled conditions (Grzesiak 1997;Sánchez et al 1998; Iglesias-García et al 2012a, b).…”
Section: Plant Materials and Growth Conditionsmentioning
confidence: 99%
“…These cultivars, all semi-dwarf, were selected on the basis of previous studies according to their possible tolerance or susceptibility to water stress in controlled conditions (Grzesiak 1997;Sánchez et al 1998; Iglesias-García et al 2012a, b).…”
Section: Plant Materials and Growth Conditionsmentioning
confidence: 99%
“…Differences in stomatal resistance and leaf water status were shown when legume varieties were exposed to drought (Grzesiak et al, 1997) and water conservation was attributable to efficient stomatal regulation in legumes (Amede & Schubert, 2003b).…”
Section: Gas Exchangementioning
confidence: 99%
“…Turner et al (2001) identified rooting depth and density as a main drought avoidance trait in grain legumes for use in terminaldrought environments. Grzesiak et al (1997) showed that drought resistant faba bean and pea cultivars had extensive and prolific root systems.…”
Section: Root Characteristicsmentioning
confidence: 99%
“…According to Li et al (1999), drought stress during the growth stage can result in fewer roots, accelerate the aging of the aboveground components, and decrease root biomass production and raw cotton yield. Both total root length and dry matter accumulation of soybean roots were found to decline in arid treatments (Grzesiak et al, 1997). Under the arid soil condition with low precipitation in 2015, the film mulching treatment played a role in conserving soil moisture, whereas soil with the film removal treatment was under excessive drought stress.…”
Section: Cotton Root Dry Matter Accumulation With Mulch Film Removal mentioning
confidence: 94%